Perencanaan Strategi Infrastruktur Teknologi Informasi Menggunakan Metode Ward and Peppard : Studi Kasus Perusahaan Skincare Lokal - Muhamad Alwi Khoerul Mufti; Karina Puspita Prameswari; Ayu Widyaningsih, Dyah; Siti Nur Kharisma Akbar (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
The development of information technology (IT) has become a crucial element in improving operational efficiency and business competitiveness in the digital era. This study aims to design an information technology infrastructure strategy for a local skincare company that currently still faces obstacles due to fragmented communication processes and manual data recording. The research method uses the Ward and Peppard framework, supported by SWOT and Value Chain analysis to identify the internal and external business environment and formulate an IS/IT strategy that aligns with the business strategy. The research approach is descriptive qualitative through interviews, observations, and literature studies. The analysis results indicate that the main problem lies in the lack of infrastructure capable of integrating production, distribution, and inventory management processes. Based on these findings, this study recommends designing an infrastructure strategy that supports the implementation of the integrated system "Sivendor". This system functions as a hub that connects workflows between production vendors, warehouses, and sales departments. In conclusion, this study produces a blueprint for an adaptive IT infrastructure strategy as a technical foundation to minimize data errors, improve operational efficiency, and support real-time decision-making.